Efektivitas Edukasi Self Care terhadap Kepatuhan Pengobatan pada Pasien Diabetes Mellitus Type II: Literature Review: The Effectiveness of Self-Care Education on Medication Adherence in Patients with Type 2 Diabetes Mellitus: A Literature Review - Ricky Riyanto Iksan; Daimah; Havis Dwi Safitri; Isa Chanifah; Siti Masruroh (Journal of Nursing Education and Practice, 2026)
Introduction: Diabetes mellitus (DM) is a chronic disease characterized by elevated blood glucose levels due to impaired insulin function, impaired insulin secretion, or a combination of both. This disease requires long-term management to prevent acute and chronic complications. Although DM cannot be cured, blood sugar levels can be controlled through the four main pillars of diabetes management: education, diet, physical activity, and pharmacological therapy. Effective self care education is considered an essential strategy to improve patients' ability to manage their condition and reduce the risk of diabetes-related complications.Objectives: This study aims to examine the effectiveness of Diabetes Self-Management Education (DSME) on medication adherence and blood sugar control in patients with Type 2 Diabetes Mellitus through a literature review.Method: This study used a literature review method by searching for scientific articles published between 2021 and 2026 through the Google Scholar database. The search was conducted using the PICO approach, namely P (Population): Type 2 Diabetes Mellitus patients; I (Intervention): self-care education or Diabetes Self-Management Education (DSME); C (Comparison): standard care or without self-care education; and O (Outcome): increased medication adherence in Type 2 Diabetes Mellitus patients. Articles were selected based on predetermined inclusion and exclusion criteria using the PRISMA flow.Result: Based on an analysis of six articles that met the inclusion criteria, self-care education was found to be effective in improving medication adherence, self-care ability, self-management, self-efficacy, quality of life, and blood glucose control among patients with Type 2 Diabetes Mellitus.Conclusion: Based on the review of the six selected articles, it can be concluded that Diabetes Self-Management Education (DSME) is an effective intervention to improve medication adherence, strengthen self-care behaviors, and support better blood glucose control in patients with Type 2 Diabetes Mellitus.